Exploring the potential of generative AI in education: a critical examination of personalised learning with ChatGPT - Looi, Chee Kit (2024)
The integration of Generative AI, particularly through tools like ChatGPT, into educational settings has been heralded for its potential to revolutionize personalized learning (PL). This presentation delves into the promises and realities of employing chatbot technologies for PL. Through a design study focused on graduate student interactions with a tutor bot during discussions on educational reforms, we critically assess the current capabilities and limitations of ChatGPT in facilitating personalized learning. Our investigation highlights the power and limitations of these tools for supporting educational objectives while identifying gaps and opportunities for future enhancements.